BRICS: Walking Towards a Common Security Agenda - Porto, Luis Filipe de Souza (Conjuntura Global, 2015)
The main purpose of this paper is to show how each BRICS country can concatenate its international security interests in order to shape a common security agenda among the group. Thus, the purpose is to elucidate that the group can play a decisive and deeper role not only in economic issues, but also in other important international affairs. Key-words: BRICS; International Security Agenda; Multilateralism.